The Antipsychotic Thioridazine Shows Promising Therapeutic Activity in a Mouse Model of Multidrug-Resistant Tuberculosis - van Soolingen, Dick; Hernandez-Pando, Rogelio; Orozco, Hector; Aguilar, Diana; Magis-Escurra, Cecile; Amaral, Leonard; van Ingen, Jakko; Boeree, Martin J. (PloS one, 2010)
Multidrug- and extensively drug-resistant tuberculosis have emerged as grave threats to public health worldwide. Very few active drugs are available or likely to become available soon. To address these problems we revisited a classical observation, the applicability of phenothiazines as antimicrobial drugs. Within this pharmacological class we selected thioridazine, which is most efficacious and least toxic, when used as an antipsychotic drug. We tested thioridazine monotherapy in the Balb/c mouse model for its activity to treat both susceptible and multidrug-resistant tuberculosis by a two months daily oral administration of 32 and 70 mg/kg. In addition, we tested its additive value when combined with a standard first-line regimen for susceptible tuberculosis. Thioridazine treatment resulted in a significant reduction of colony-forming-units of the susceptible (-4.4 log CFU, p<0.05) and multidrug-resistant tuberculosis bacilli (-2.4 log CFU, p<0.009) in the lung both at one and two months after infection, compared to controls. Moreover, when thioridazine was added to a regimen containing rifampicin, isoniazid and pyrazinamide for susceptible tuberculosis, a significant synergistic effect was achieved (-6.2 vs -5.9 log CFU, p<0.01). Thioridazine may represent an effective compound for treatment of susceptible and multidrug-resistant tuberculosis. The phenothiazines and their targets represent interesting novel opportunities in the search for antituberculosis drugs.